2019
DOI: 10.3390/jcm8060896
|View full text |Cite
|
Sign up to set email alerts
|

Early Local Inhibition of Club Cell Protein 16 Following Chest Trauma Reduces Late Sepsis-Induced Acute Lung Injury

Abstract: Blunt thoracic trauma (TxT) deteriorates clinical post-injury outcomes. Ongoing inflammatory changes promote the development of post-traumatic complications, frequently causing Acute Lung Injury (ALI). Club Cell Protein (CC)16, a pulmonary anti-inflammatory protein, correlates with lung damage following TxT. Whether CC16-neutralization influences the inflammatory course during ALI is elusive. Ninety-six male CL57BL/6N mice underwent a double hit model of TxT and cecal ligation puncture (CLP, 24 h post-TxT). Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…In this study, mice were treated with anti-CC-16 antibodies or IgG directly after trauma. Early anti-CC-16 treatment was associated with more neutrophil infiltration and more damaged lung tissue compared with IgG vehicle-treated mice 40. Taken together, in the present study MODS seemed more related to anti-inflammatory proteins than to proinflammatory proteins.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, mice were treated with anti-CC-16 antibodies or IgG directly after trauma. Early anti-CC-16 treatment was associated with more neutrophil infiltration and more damaged lung tissue compared with IgG vehicle-treated mice 40. Taken together, in the present study MODS seemed more related to anti-inflammatory proteins than to proinflammatory proteins.…”
Section: Discussionsupporting
confidence: 53%
“…For TxT, mice underwent general mask anesthesia with 3% isoflurane (Baxter Deutschland GmbH), according to partly-modified standardized protocols described previously ( 7 , 9 , 10 , 27 ). Briefly, the mice were placed in the supine position under a cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the findings of other researchers, it was found that isolated experimental lung trauma induced a profound inflammatory reaction; however, it was insufficient to establish the ongoing pathological pulmonary changes associated with ALI ( 7 , 8 ). However, secondary CLP following TxT, as applied herein, reflected the human etiology of indirect lung damage ending in ALI ( 7 , 9 - 11 ). Another murine 'double-hit' model that includes CLP, followed by inducing pneumonia via Pseudomonas aeruginosa 4-7 days later, significantly improved survival when pneumonia was induced after 7 days.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Störmann and colleagues [17] studied a biomarker named club cell protein 16 (CC16) deriving from lung epithelial club cells that has anti-inflammatory tasks. The systemic concentrations of CC correlate with the extent of pulmonary contusion in traumatized patients.…”
mentioning
confidence: 99%